2014
DOI: 10.1159/000355175
|View full text |Cite
|
Sign up to set email alerts
|

Increased Severity of Inflammation Correlates with Elevated Expression of TRPV1 Nerve Fibers and Nerve Growth Factor on Interstitial Cystitis/Bladder Pain Syndrome

Abstract: Objectives: Although evidence supports a role for inflammation in interstitial cystitis/bladder pain syndrome (IC/BPS), the mechanism remains unknown. We determined whether inflammation causes an elevated expression of nerve growth factor (NGF) and transient receptor potential vanilloid receptor subtype 1 (TRPV1) and correlated them with the symptoms. Methods: Bladder biopsies were obtained from 53 IC/BPS patients and 27 controls, and hematoxylin and eosin staining, immunostaining and Western blotting were per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 28 publications
(50 reference statements)
0
53
0
Order By: Relevance
“…BoNT/A1 injection for overactive bladder treatment is also associated with a significant decrease of purinergic receptors P2X3 and capsaicin receptors TRPV1, two receptors involved in nociception in the suburothelial nerve fibers (Apostolidis et al, 2005; Liu et al, 2014). These changes may reflect a direct activity of BoNT on the afferent innervation of the bladder and/or a secondary effect on the efferent innervation of the detrusor.…”
Section: Pharmacologymentioning
confidence: 99%
“…BoNT/A1 injection for overactive bladder treatment is also associated with a significant decrease of purinergic receptors P2X3 and capsaicin receptors TRPV1, two receptors involved in nociception in the suburothelial nerve fibers (Apostolidis et al, 2005; Liu et al, 2014). These changes may reflect a direct activity of BoNT on the afferent innervation of the bladder and/or a secondary effect on the efferent innervation of the detrusor.…”
Section: Pharmacologymentioning
confidence: 99%
“…Consistently, increased severity of inflammation correlates with upregulation of TRPV1 in bladder nerve fibers of BPS/IC patients (Liu et al. ). These findings suggest that enhanced function or upregulation of TRPV1 in bladder sensory neurons may be responsible for the increased RTX‐evoked nociceptive behaviors in the H 2 O 2 ‐induced rat cystitis model.…”
Section: Discussionmentioning
confidence: 60%
“…We found that BPS/IC was significantly associated with previous statin use, and the Although there is no consensus on a mechanism to explain the underlying cause of BPS/IC, several pathophysiologic mechanisms have been proposed, including epithelial dysfunction, mast cell activation, and neurogenic inflammation [19][20][21] . In addition, many recent studies reported that a higher level of cell apoptosis in the urothelium was associated with inflammation in patients with BPS/IC [22][23][24][25] .…”
Section: Discussionmentioning
confidence: 99%